2019
DOI: 10.1002/cncr.32207
|View full text |Cite
|
Sign up to set email alerts
|

Update on triple‐negative breast cancer disparities for the United States: A population‐based study from the United States Cancer Statistics database, 2010 through 2014

Abstract: BACKGROUND: Triple-negative breast cancer (TNBC) has been associated with a more aggressive histology, poorer prognosis, and nonresponsiveness to hormone therapy. It is imperative that cancer research identify factors that drive disparities and focus on prevention. METHODS: Using the United States Cancer Statistics database, the authors examined differences between TNBCs compared with all other breast cancers with regard to age, race/ethnicity, and stage at diagnosis. RESULTS: A total of 1,151,724 cases of bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(97 citation statements)
references
References 25 publications
5
91
0
1
Order By: Relevance
“…In one of the very few related studies conducted to date, Taylor and colleagues found that more frequent experiences of everyday discrimination were associated with an increased risk of incident breast cancer among Black Women's Health Study participants, particularly those under the age of 50 [34]. However, they did not separate breast cancer cases by subtype, so it is unclear as to whether the observed age stratification is due to age-specific variation in the risk associated with discrimination, or if the results are confounded by the well-established increased risk of TNBC among younger women [10]. Innovative work by Krieger et al did not directly measure interpersonal discrimination, but rather structural racism via the legal codification of racial discrimination in states with Jim Crow laws.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In one of the very few related studies conducted to date, Taylor and colleagues found that more frequent experiences of everyday discrimination were associated with an increased risk of incident breast cancer among Black Women's Health Study participants, particularly those under the age of 50 [34]. However, they did not separate breast cancer cases by subtype, so it is unclear as to whether the observed age stratification is due to age-specific variation in the risk associated with discrimination, or if the results are confounded by the well-established increased risk of TNBC among younger women [10]. Innovative work by Krieger et al did not directly measure interpersonal discrimination, but rather structural racism via the legal codification of racial discrimination in states with Jim Crow laws.…”
Section: Discussionmentioning
confidence: 98%
“…Breast cancer subtype is intrinsic to tumor development [7], making it an early and important source of inequality. Relative to White women, Black women with breast cancer are twice as likely to be diagnosed with triple-negative breast cancer (TNBC), defined as tumors that are lacking or express very low levels of estrogen receptors (ER), progesterone receptors (PR), and human epidermal growth factor receptor 2 (HER2) [8][9][10]. Women with TNBC are more likely to have larger and higher grade tumors, a shorter time to relapse, and lower survival rates than women with ER and/or PR positive (referred to as hormone receptor positive, or HR+), HER2 negative (HER2−) tumors [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, death rates for blacks are 1.9‐2.6 times higher than for whites in the age groups ≤ 50 years but 1.1‐1.2 times higher in the groups aged 70 to 79 years and ≥80 years. Greater racial disparities in younger women may in part reflect the higher proportion of triple‐negative breast cancers that are diagnosed in younger women …”
Section: Selected Findingsmentioning
confidence: 99%
“…Greater racial disparities in younger women may in part reflect the higher proportion of triple-negative breast cancers that are diagnosed in younger women. 19 Incidence rates for breast cancer subtypes Racial/ethnic variations in incidence rates by breast cancer subtype and age are shown in Figure 4. Among women 20 years and older, incidence rates of HR-positive/HER2negative breast cancer are highest in white women (138 cases per 100,000), with rates 23% higher than in blacks (112 per 100,000) and about 45% higher than in Hispanics and AIANs, who have the lowest incidence rates (94-97 per 100,000).…”
Section: Cancer Occurrence In the Most Recent Time Periodmentioning
confidence: 99%
“…In addition, standard breast cancer screening methods like mammography cannot determine the magnitude of severity or molecular characteristics of breast tumors (i.e., TNBC status) resulting in a need for additional molecular testing. Such testing to date has not yet been extensively developed despite the fact that TNBC makes up about 15%-20% of breast cancer cases and results in a disproportionate number of breast cancer deaths 3 . Therefore, the concept of developing accurate ways to detect TNBC before it becomes invasive has been proposed.…”
Section: Discussionmentioning
confidence: 99%